IER. CONGRESO PANAMERICANO DE INTERDISCIPLINA - Kertész, Roberto (European Scientific Journal, ESJ, 2015)
Over 2000 clinical cases related to early suicidal decisions were studied at the Private Institute of Clinical Psychology. A greater majority of such cases occurs during childhood under parental influences, which was generally non-verbal. In this paper, the preventive value was stressed